REKONSTRUKSI PENYELESAIAN SENGKETA ADMINISTRASI DAN HASIL PEMILIHAN GUBERNUR, BUPATI DAN WALIKOTA - Much. Anam Rifa'i (Arena Hukum, 2014)
Abstract Administrative dispute resolution, as well as results in elections for governor, regent and mayor today, may raise many legal issues. Some of such issues are the State Administrative Court’s inexecutable decision’s, the decision’s contradicting dualism and legal disharmony during stages of election. These problematic issues can lead to legal uncertainty, public confusion as well as potency for horizontal conflict. Therefore, an immediate  recontruction of both administrative dispute resolution and results in election for governor, regent and mayor needs to be conducted. Through the prespective of normative legal study, it is concluded that in the future, there should be readjustments of stages in elections for governor, regent, and mayor by regarding the time constraints to solve any matter of dispute within the legal boundaries of Election Supervisory Board at provincial an regencial level or State Administrative Court’s, as well as reevaluations in authorizing other form of legal institutions to solve any dispute regarding the elections results.Key words: reconstruction, administrative dispute and results in elections for governor, regent and mayor, elections for governor, regent and mayorelection  Abstrak Penyelesaian sengketa administrasi dan hasil pemilihan gubernur, bupati dan walikota yang selama ini sudah dilaksanakan menimbulkan banyak permasalahan hukum. Beberapa di antaranya adanya putusan PTUN yang tidak bisa dieksekusi, dualisme putusan badan peradilan yang saling bertentangan serta disharmonisasi hukum acara PTUN dengan tahapan pemilihan. Permasalahan tersebut menyebabkan terjadinya ketidakpastian hukum,  kebingungan masyarakat, serta berpotensi menimbulkan konflik horizontal. Oleh sebab itu rekonstruksi sistem penyelesaian sengketa administrasi dan hasil pemilihan gubernur, bupati dan walikota mutlak dilakukan. Melalui penelitian hukum normatif disimpulkan, ke depan harus ada penyusunan ulang tahapan pemilihan gubernur, bupati dan walikota dengan memperhatikan limitasi waktu penyelesaian sengketa di Bawaslu provinsi/Panwaslu Kabupaten/Kota maupun di PTUN, serta melakukan peninjauan kembali pengaturan pemberian wewenang kepada badan peradilan selain Peradilan Tata Usaha Negara untuk menyelesaikan sengketa hasil pemilihan gubernur, bupati dan walikota.Kata kunci: rekonstruksi, sengketa administrasi dan hasil pemilihan gubernur, bupati dan walikota, pemilihan gubernur, bupati dan walikota